Africa’s Urban Revolution - Tarrósy, István (Afrika Tanulmányok / Hungarian Journal of African Studies, 2018)
Tarrósy István a következő művet mutatta be: Susan Parnell – Edgar Pieterse (eds.): Africa’s Urban Revolution. London: Zed Books. 2014. pp. 309.